Long term studies on the utilisation of quartz sandstone wastes in cement concrete. (1st February 2017) - Kumar, Sanjeev; Gupta, Ramesh Chandra; Shrivastava, Sandeep
Abstract: Disposal of stone wastes has become one of the major environmental problems in the world. The use of marbles, granites and sandstones as a building material has increased and the disposal of unused stones possess a severe threat to the society. Every year tonnes of stone wastes have been generated, and it was estimated that almost 25% of stone goes as wastes while processing and cutting them. Over the years, the quarrying area has expanded, and the use of modern machinery had led to the cutting of hardest of stones and exposing the soft underbelly of sandstones. One of the possible solutions for the utilisation of these sandstone wastes is to incorporate them into cement concrete as the replacement for natural coarse aggregates. This paper presents the results of experimental research to examine the suitability of quartz sandstone as a substitute for natural coarse aggregates in cement concrete. The quartz sandstone wastes were used in definite percentages and replaced for coarse aggregates from 0% to 100% at every 20% interval. The article presents with tests such as pull off strength, carbonation, sulphate attack, porosity and extended results of compressive strength, flexural strength. It was observed that the compressive strength, flexural strength and the sulphate attack resistance were lower than that of control concrete; but upto a certain level of replacement, they showed better resistance to pull off and carbonation. Also, the decrease in strength was found to be comparable to that of control specimens. It was concluded that there is a propitious future for the use of quartz sandstone wastes as a partial substitute for natural coarse aggregates in concrete, which can lead to a greater environmental and sustainable benefits. Highlights: Quartz sandstone (mine waste) is used in cement concrete. The waste was replaced for conventional coarse aggregates. M30 concrete grade was used for study. Water cement ratios of 0.35, 0.4 and 0.45 were adopted. Long term tests such as carbonation, sulphate attack was studied. Extended mechanical strength (compression and flexural) tests were carried out.